Presence, Fate, and Behaviour of Emerging Micropollutants in the New Zealand and Antarctic Coastal Environment - Emnet, Philipp Johannes (University of Canterbury. Chemistry, 2013)
Many chemicals used in everyday personal care products are today amongst the most commonly detected compounds in surface waters throughout the world. Collectively referred to as micropollutants, they include paraben preservatives, organic UV filters, alkylphenols, triclosan, and bisphenol-A. Micropollutants enter the aquatic environment predominantly via wastewater discharges. To date there has been only limited assessments on their presence and impacts in coastal environments. The wastewater treatment plants in Lyttelton, Governors Bay, and Diamond Harbour were found to discharge micropollutants into Whakaraupo Harbour. Similarly, the sewage effluents of the Antarctic research stations Scott Base and McMurdo Station were found to discharge micropollutants into Erebus Bay. Strong seasonal changes in the Whakaraupo effluent concentrations were observed, with concentrations higher in winter than in summer. Concentrations fluctuated greatly in Scott Base, reaching concentrations higher than have been previously reported internationally. The nine most commonly detected analytes were octylphenol, 4-MBC, BP-3, BP-1, triclosan, methyl triclosan, bisphenol-A, estrone, and coprostanol. The marine environments in Whakaraupo Harbour and Erebus Bay were found to be similarly impacted. The most commonly detected micropollutants in seawater in Whakaraupo Harbour were mParaben, 4-MBC, BP-3, OMC, bisphenol-A, and estrone. The marine sediments in Whakaraupo Harbour accumulated mParaben, octylphenol, 4-MBC, BP-3, BP-1, bisphenol-A, OMC, estrone, and coprostanol, while mussels bioaccumulated mParaben, octylphenol, and BP-3. The same range of micropollutants were detected in seawater throughout Erebus Bay, including the reference sites. Marine biota (clams, urchins, and fish), including those from the reference site, were shown to readily bioaccumulate mParaben, pParaben, octylphenol, BP-3, E2, EE2, and coprostanol. A much larger coastal area of Antarctica and New Zealand is therefore impacted than was previously thought. ...